World catalog of extant and fossil Chaoboridae (Diptera) - Borkent, Art (Zootaxa, 2014)
A world catalog of extant and fossil Chaoboridae provides full type information, distribution of each species, references to keys, references to latest descriptions of each species, and summaries of bionomic information.  There are 51 extant species in six genera and 41 fossil species (2 unplaced) in 19 genera, two of which are extant. Chaoborus lanei (Belkin, Heinemann & Page) is a new synonym of C. braziliensis (Theobald) and C. annulatus Cook is a new synonym of C. festivus Dyar & Shannon.